discourse and power relations in the constitution of gender identities: a theoretical discussion based on Michel Foucault and Judith Butler - Mattos, Georgia; Cajueiro Santos, Tarcyanie (Passagens: Revista do Programa de Pós-Graduação em Comunicação da Universidade Federal do Ceará, 2024)
This article seeks to problematize the premises that permeate the cultural configurations that regulate and produce gender identities, through legitimizing discourses that produce “truths” for gender identities. This is an excerpt from the thesis “Subversive strategies in the discourse of YouTuber Louie Ponto on gender relations: a Critical Discourse Analysis”, which presents the theoretical discussion of the research, carried out based on Michel Foucault and Judith Butler. In this way, an interconnection is proposed between the concepts of sexuality dispositif, in Foucault, and gender performativity, in Butler, traversed by the relations of power and knowledge, discussed in the field of Communication and Culture. Thus, a clear articulation between power and knowledge is observed in the discourse that constitutes the performativity of genders, since power creates objects of knowledge.